Diagnostic Stability of Primary Psychotic Disorders in a Research Sample - Wood, Andrea J.; Carroll, Amber R.; Shinn, Ann K.; Ongur, Dost; Lewandowski, Kathryn E. (Frontiers in Psychiatry, 2021)
Psychiatric diagnosis is often treated as a stable construct both clinically and in research; however, some evidence suggests that diagnostic change may be common, which may impact research validity and clinical care. In the present study we examined diagnostic stability in individuals with psychosis over time. Participants with a diagnosis of any psychotic disorder (n=142) were assessed at two timepoints using the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders. We found a 25.4% diagnostic change rate across the total sample. People with an initial diagnosis of psychosis not otherwise specified and schizophreniform disorder had the highest rates of change, followed by those with schizophrenia and schizoaffective disorder; people with bipolar disorder had the lowest change rate. Most participants with an unstable initial diagnosis of schizophrenia, schizophreniform disorder, bipolar disorder, or psychosis not otherwise specified converted to a final diagnosis of schizoaffective disorder. Participants with an unstable initial diagnosis of schizoaffective disorder most frequently converted to a diagnosis of schizophrenia. Our findings suggest that diagnostic change is relatively common, occurring in approximately a quarter of patients. People with an initial diagnosis of schizophrenia-spectrum disorder were more likely to have a diagnostic change, suggesting a natural stability of some diagnoses more so than others.